2022
DOI: 10.21037/atm-21-3897
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of miR-651-5p inhibits ultraviolet radiation-induced malignant biological behaviors of sebaceous gland carcinoma cells by targeting ZEB2

Abstract: Background Ultraviolet (UV) exposure is the most essential etiological factor in sebaceous gland carcinoma (SGC). The abnormal expression of microRNAs (miRNAs) is also involved in SGC. However, the function of miRNAs in UV-induced SGC is still unclear. Methods In this study, the expression levels of miR-651-5p and zinc finger E-box binding homeobox 2 ( ZEB2 ) in SGC tissues and cells were measured by real-time quantitative polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Also, a study has reported that overexpression of miR‐651‐5p suppresses SGC cell malignant actions. More specifically, miR‐651‐5p not only promotes cell apoptosis but also inhibits the invasive and migratory ability and epithelial‐mesenchymal transition of ultraviolet‐induced SGC cells 8 . Collectively, our study findings are in conformity with these study outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, a study has reported that overexpression of miR‐651‐5p suppresses SGC cell malignant actions. More specifically, miR‐651‐5p not only promotes cell apoptosis but also inhibits the invasive and migratory ability and epithelial‐mesenchymal transition of ultraviolet‐induced SGC cells 8 . Collectively, our study findings are in conformity with these study outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…miRNAs are good candidates as biomarkers for lung cancer 7 . For example, miR‐651‐5p expression is associated with sebaceous gland carcinoma (SGC) malignant behaviors 8 . It is also suggested that miR‐651‐5p expression has an association with colorectal cancer (CRC) 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article ( 1 ) titled “Overexpression of miR-651-5p inhibits ultraviolet radiation-induced malignant biological behaviors of sebaceous gland carcinoma cells by targeting ZEB2 ” (doi: 10.21037/atm-21-3897), unfortunately contain errors in the authorship section, the legend of Figure 2, Figure 3 and its legend, Figure 4, Figure 5 and its legend, and the legend of Figure 7.…”
mentioning
confidence: 99%